PERSUASIVE ASSISTANCE AND PROBLEM-SOLVING FOR THE ESTABLISHMENT OF VILLAGE-OWNED ENTERPRISES - Suyanto Dr (EQUALEGUM International Law Journal, 2023)
Background. Programs from local governments to develop and prosper village communities through Village-Owned Enterprises (hereinafter better known as BUMDes) are in line with Law No. 6/2014 article 1 paragraph 6. However, the establishment of BUMDes is still unknown to the village community and many problems make village communities unable to take advantage of BUMDes. The purpose of this activity was to 1) increase knowledge of Tanjung village communities about BUMDes, 2) determine village potential, establishment, and management of BUMDes. Implementation Method. This community service activity was in collaboration with the Lamongan Government Sector and Indonesian Notary Association of East Java Regional Management through "Notary Masuk Desa" program. This activity was carried out in Tanjung Village, Lamongan Regency. This activity starts from providing seminars to village leaders and the Tanjung Village community on how to establish BUMDes until the establishment of BUMDes. Assistance related to all problems while managing BUMDes and providing legal or economic solutions. Findings. BUMDes and Tanjung Village business units that were formed include village electricity businesses, electricity payment services, and agricultural production facilities, providing credit/loans that are easily accessible to the community. During the running period of 6 months, the business unit was running well and problems began when village capital was still used by the credit business unit and the legality aspects of the village business unit that had been formed. Conclusion. BUMDes requires transparent, active, and integrity management to be following the purpose of its formation to improve the economy of the village and community.